Свойство робастности и запасы устойчивости линейных систем - Дубовик, С.А. (Проблемы управления и информатики, 2007)
Для лінійних систем розглянуто можливість представлення робастних властивостей за допомогою критичної величини малого параметра сингулярних збурень. Наведено приклади для систем з «повільною» компонентою невисокого порядку. For the linear systems possibility of presentation of robust properties is examined by the critical size of small parameter of singular perturbations. Examples are given for the systems with «slow» component of low order.